1996
DOI: 10.1063/1.872064
|View full text |Cite
|
Sign up to set email alerts
|

Resistive destabilization of cycloidal electron flow and universality of (near-) Brillouin flow in a crossed-field gap

Abstract: It is shown that a small amount of dissipation, caused by current flow in a lossy external circuit, can produce a disruption of steady-state cycloidal electron flow in a crossed-field gap, leading to the establishment of a turbulent steady state that is close to, but not exactly, Brillouin flow. This disruption, which has nothing to do with a diocotron or cyclotron instability, is fundamentally caused by the failure of a subset of the emitted electrons to return to the cathode surface as a result of resistive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 13 publications
1
34
0
Order By: Relevance
“…(9) below) and can be taken as an opposite limit. Important features of sheet charge models appear in the works of Kishek and Lau 30 and Christenson et al 31 The present approach summarizes key points. Let the position of the sheet in the AK gap be specified by x ¼ sD, where 0 s 1 is a scaled position.…”
Section: A Transit Time Approximationmentioning
confidence: 97%
“…(9) below) and can be taken as an opposite limit. Important features of sheet charge models appear in the works of Kishek and Lau 30 and Christenson et al 31 The present approach summarizes key points. Let the position of the sheet in the AK gap be specified by x ¼ sD, where 0 s 1 is a scaled position.…”
Section: A Transit Time Approximationmentioning
confidence: 97%
“…In previous 1D simulations of nonrelativistic, cycloidal crossed-field flows using the electrostatic code PDP1, 23 it is found that a small ac gap voltage, 3,26 or a small external resistance, 27 or a small misalignment in the external magnetic field, 28 may render the cycloidal flow unstable even when the emission current density is only a small fraction of the critical values depicted in Fig. 2.…”
Section: Remarksmentioning
confidence: 96%
“…10 The classical 1D model was also extended to a quantum model for a nanosized crossed-field gap. 11 For the B ജ B H case, it was found that transition from laminar flow to turbulent flow may occur due to over injection of current with a value higher than the limiting current value, 9 small ac voltage modulation, 12 resistivity, 13 and misalignment of the magnetic field. 14 The microwave magnetron is a type of crossed-field device that is widely used in microwave ovens, radars, industrial heating, medical accelerators, and plasma sources.…”
mentioning
confidence: 98%